1998
DOI: 10.1161/01.atv.18.2.316
|View full text |Cite
|
Sign up to set email alerts
|

Similar Effects of Diets Rich in Stearic Acid or trans -Fatty Acids on Platelet Function and Endothelial Prostacyclin Production in Humans

Abstract: Abstract-The effects of stearic acid (C18:0) and trans-fatty acids (trans-FAs) on measures of platelet function and prostacyclin (PGI 2 ) production are poorly understood in humans. In this controlled dietary study, platelet function and endothelial PGI 2 production were studied in healthy humans after they consumed diets rich in C18:0 or trans-FAs. For 5 weeks, 80 subjects consumed a baseline diet high in saturated FAs and were then switched to a diet containing 9.3% of energy as stearic acid or a diet contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 46 publications
1
16
0
1
Order By: Relevance
“…In line with previous studies (Wennmalm et al, 1991;Nowak et al, 1987;Barrow et al, 1989), a trend for increased excretion was seen in smokers, whereas the wheat bread and rye bread diets did not differ. Although we could ®nd no differences between the two bread periods, dietary factors, namely dietary fatty acid composition, has been shown to affect excretion of thromboxane metabolites in several studies (Ferretti et al, 1993;Prakash et al, 1994, Turpeinen et al, 1998a.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In line with previous studies (Wennmalm et al, 1991;Nowak et al, 1987;Barrow et al, 1989), a trend for increased excretion was seen in smokers, whereas the wheat bread and rye bread diets did not differ. Although we could ®nd no differences between the two bread periods, dietary factors, namely dietary fatty acid composition, has been shown to affect excretion of thromboxane metabolites in several studies (Ferretti et al, 1993;Prakash et al, 1994, Turpeinen et al, 1998a.…”
Section: Discussionmentioning
confidence: 60%
“…The urine was stored in 10 ml tubes at 720 C. The analysis of 2,3-dinor-TXB 2 was carried out from pooled 3-day samples. After sample puri®cation by the method of Berens et al (1984) the samples were analysed for 2,3-dinor-TXB 2 with enzyme immuno assay (EIA) as previously described (Turpeinen et al, 1998a(Turpeinen et al, ,1998b.…”
Section: Dietmentioning
confidence: 99%
“…To date, the data reported by various authors on the effect of dietary stearic acid on platelet aggregation are con¯icting. It has been demonstrated that, for a particular dietary fatty acid, the aggregatory response to the same agonist can give opposing results (Turpeinen et al, 1998;Kwon et al, 1991), due partly to the medium in which platelets have been assessed. There is argument as to whether whole blood or platelet-rich plasma (PRP) samples are more appropriate for determination of ex vivo aggregation, or as a model to represent the in vivo situation.…”
Section: Discussionmentioning
confidence: 99%
“…The data reported by various authors on the effect of dietary stearic acid on platelet aggregation have been conflicting. It has been demonstrated that for a particular dietary fatty acid, the aggregatory response to the same agonist can give opposing results (Kwon et al, 1991;Turpeinen et al, 1998), which may be due partly to the medium in which platelet aggregation has been studied. There is some debate among researchers as to whether in vitro platelet aggregation in whole blood or using platelet-rich plasma is more appropriate.…”
Section: Discussionmentioning
confidence: 99%